Factors associated with strong opioid use for noncancer pain in patients with chronic intestinal failure. (2nd October 2022) - Deutsch, Liat; Cloutier, Anabelle; Leahy, Gavin; Teubner, Antje; Abraham, Arun; Taylor, Michael; Paine, Peter; Lal, Simon
Abstract: Background: Chronic analgesic use is described in home parenteral nutrition (HPN)–dependent patients, but there are limited data on factors associated with opioid use for noncancerous pain. Methods: Patients attending a national UK intestinal failure reference center were divided in two groups according to strong opioid (SO) usage; risk factors for SO usage were analyzed using logistic regression. Results: A total of 168 HPN‐dependent patients were included. During the study period, 73 patients (43.5%) had documented SO usage (SO group), whereas the remainder did not (No‐SO group). The prevalence of Crohn's disease among the No‐SO group was twofold higher than among the SO group (43.2% vs 24.7%; P = 0.013), whereas those with surgical complications were twice as prevalent among the SO group (19.2% vs 8.4%, respectively; P = 0.04). The rate of working‐age unemployment was significantly higher in the SO group (90.6%) than the No‐SO group (55.6%; P = 0.001). Multivariate regression showed unemployment as an independent risk factor for SO usage (OR, 6.005; 95% CI, 1.435–25.134), whereas Crohn's disease (OR, 0.284; 95% CI, 0.09–0.898) and <4 intravenous support (IVS) nights per week (OR, 0.113; 95% CI, 0.012–1.009) were protective factors. The life‐long incidence of catheter‐related bloodstream infection (CRBSI) was comparable between groups (34.2% SO vs 27.4% No‐SO; P = 0.336). Conclusion: SO use is frequent among HPN‐dependent patients and associated with high rates of unemployment and ≥4 IVS nights per week, but not with increased rate of CRBSI. The reduced usage among patients with Crohn's disease warrants further evaluation but might be due to the chronicity as compared with other IF etiologies.